The relative effects of self-reported noise and odour annoyance on psychological distress: Different effects across sociodemographic groups? - Eline Berkers (Public Library of Science (PLoS), 2021)
In earlier research, both higher levels of noise and odour annoyance have been associated with decreased mental health. Presumably, these perceptions can trigger feelings of threat and stress reactions and in turn evoke psychological distress. There are two important lacunas in the research on this topic: most studies only consider either noise or odour annoyance and not their relative effect on psychological distress and there is scarce evidence about whether different sociodemographic groups experience more psychological distress due to noise and odour annoyance. Starting from the diversity in the available coping resources and in their daily life patterns, we distinguish gender, age and educational level as relevant sociodemographic variables. Using data from the Health Monitor (n = 25236) in Noord-Brabant, we found using Ordinary Least Squares Regression that individuals that reported higher levels of noise and odour annoyance reported higher levels of psychological distress. Furthermore, the effect of noise annoyance was relatively stronger compared to that of odour annoyance. Regarding the interaction effects, we found that younger adults' psychological distress was more strongly affected by noise annoyance compared to older adults, but not by odour annoyance. The psychological distress of individuals with no or primary education was more strongly affected by both noise and odour annoyance compared those with tertiary education, but not when compared to those who completed lower or higher secondary education. Contrary to our expectations, we did not find different effects between men and women. Though the evidence for the interactions was mixed, classic health inequalities along age and education lines are reinforced when considering the relationship between noise and odour annoyance and psychological distress.